Migration Processes Provoked yy the Break-Up of Yugoslavia and the Agression against Croatia - Mirjana Domini (Migracijske i etničke teme, 1999)
The paper deals with forced migration caused by Serb aggression in areas of Croatia and the neighbouring countries. The first part presents the relevant facts relating to Croatia and important for an understanding of the migration flows (some demographic data as well as the basic guidelines of migration policy, legal regulations and most important problems connected with expellees, refugees and displaced persons). The main elements of contemporary migration movements in Croatia are indicated – migration based on economic causes (traditional migration), migration provoked by crisis and war destruction in former Yugoslavia and migration flows that are difficult to register (mainly clandestine crossings of the border of the Republic of Croatia and the irregular labour market). The author states that the expellee, refugee and displaced persons crisis (with psychological and material repercussions) began in 1991 and reached a climax in 1992 when Croatia became one of the most pronounced refugee countries in the world, with refugees accounting for about 15% of its population. As the war crisis shifted, the areas from which intense forced migration to and from Croatia resulted also shifted as did the mechanisms for regulating these forced migrations (dual citizenship, transit visas, accords with "third countries" for accepting refugees and expellees, ways of resolving and caring for the refugee-expellee populations in the Republic of Croatia). The author concludes that even after seven years from the start of the aggression against Croatia, this humanitarian crisis among expellees, refugees and displaced persons has not yet finished, as testified by the new military conflict in Kosovo and by many open questions in regard to the future organisation of states in this crisis area as well as the creation of mechanisms for monitoring potential conflicts. A fundamental idea is expressed throughout the paper – i.e. the notion that now it is maybe more important to think of ways of integrating the people who had arrived than of the reasons that caused them to arrive. Experience so far, not only in the area of former Yugoslavia, but also in similar situations in the world, demonstrates that most "war migrants" – especially after many years of expulsion – do not return to their homes.